Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

How to Deal with Inaccurate Service Descriptions in On-The-Fly Computing: Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 23rd International Conference on Natural Language and Information Systems)
The vision of On-The-Fly Computing is an automatic composition of existing software services. Based on natural language software descriptions, end users will receive compositions tailored to their needs. For this reason, the quality of the initial software service description strongly determines whether a software composition really meets the expectations of end users. In this paper, we expose open NLP challenges needed to be faced for service composition in On-The-Fly Computing.
Keywords: Requirements Extraction; Temporal Reordering of Software Functions; Inaccuracy Compensation

Improving Classifiers for Semantic Annotation of Software Requirements with Elaborate Syntactic Structure - Kim, Yeongsu; Lee, Seungwoo; Dollmann, Markus; Geierhos, Michaela (International Journal of Advanced Science and Technology)
A user generally writes software requirements in ambiguous and incomplete form by using natural language; therefore, a software developer may have difficulty in clearly understanding what the meanings are. To solve this problem with automation, we propose a classifier for semantic annotation with manually pre-defined semantic categories. To improve our classifier, we carefully designed syntactic features extracted by constituency and dependency parsers. Even with a small dataset and a large number of classes, our proposed classifier records an accuracy of 0.75, which outperforms the previous model, REaCT.
Keywords: Software Engineering; Natural Language Processing; Semantic Annotation; Machine Learning; Feature Engineering; Syntactic Structure

Monitoring für die Bahnhofsmissionen: Ein datengestütztes Instrument zur Organisationsentwicklung. Projektbeschreibung und Ergebnisdarstellung - Goller, Michael
Keywords: Bahnhofsmission; Survey Feedback; Monitoring

Rezension von Ahrenholz, Hövelbrinks & Schmellentin (Hrsg; 2017): Fachunterricht und Sprache in schulischen Lehr-/Lernprozessen. Tübingen: Narr Franke Attempto. - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Englischnoten und globale englische Sprachkompetenz in bilingualen Zweigen - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)

Empirische Zugänge zum bilingualen Sachfachunterricht - Rumlich, Dominik (Zeitschrift für Erziehungswissenschaft)

Ein empirisch-quantitativer Blick auf „typische“ CLIL-Schüler(innen) und ihre Entwicklung - Rumlich, Dominik (Babylonia)

Current research on CLIL in the Netherlands: A discussion - Rumlich, Dominik (Dutch Journal of Applied Linguistics)

A national day of healing. Eine mündliche Prüfung als radio discussion gestalten - Matz, Frauke; Rumlich, Dominik (Der Fremdsprachliche Unterricht Englisch)